The Effect of Menarche Age on Menopause Age - Septy Ariani, Herlin Fitriana Kurniawati (International Journal of Advanced Science and Technology, 2020)
One indicator of women’s health is menarche and menopause. Every women experiences at a different age. Menopause has become a problem for a woman. Women feel worried when entering this period. Many factors cause menopause. Menarche and early menopause are the cause of death. The purpose of this study is to find out the influence of menarche age on menopause age. The method used is a Scoping Review with five stages namely problem Identification, identification of relevant studies identification, study Selection, data mapping, compiling, summarizing and reporting results. The results found from eight articles were 38% using the cohort method and 62% using the cross-sectional method. Consisting of developed countries as much as 62% and developing countries about 38%. Found four themes, namely age of women experiencing menarche, menopause, relationship between age of menarche and menopause and factors that influence it. The time of menarche result in the time of menopause. This shows that there is an influence of menarche age on menopause age.